The leopards of the domestic cat kingdom: Bengal cats / Noor Azli Affendy Lee - Affendy Lee, Noor Azli (Academy of Language Studies, 2022)
“Kucing ka? (Is that a cat?) Nampak macam harimau. (Looks like a tiger.)” That was normally the statement I got when visitors came to my house, or people in my contact list saw my WhatsApp status photos when I posted pictures of my Bengal cats. Despite their look, Bengal cats are not tigers but rather a cross between Asian leopard cats and domestic cats (Avery, 2022). Bengal cats are mostly medium to large in size and, in actuality, many are not much bigger than a normal household cat. They have an average weight of six kilograms (males are generally heavier) and can grow up to 0.4 metres long (Atrayee, 2022). However, their wild-like, exotic appear¬ance, coupled with their big and muscular body, easily attracts people’s attention, especially those who are not normally familiar in the purebred cat world. They are regarded as one of the smartest cat breeds (Atrayee, 2022).